2021
DOI: 10.3390/molecules26133841
|View full text |Cite
|
Sign up to set email alerts
|

Potential Hydrothermal-Humification of Vegetable Wastes by Steam Explosion and Structural Characteristics of Humified Fractions

Abstract: In this work, steam explosion (SE) was exploited as a potential hydrothermal-humification process of vegetable wastes to deconstruct their structure and accelerate their decomposition to prepare humified substances. Results indicated that the SE process led to the removal of hemicellulose, re-condensation of lignin, degradation of the cellulosic amorphous region, and the enhancement of thermal stability of broccoli wastes, which provided transformable substrates and a thermal-acidic reaction environment for hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…There have been studies using steam explosion to hydrolyze rutin glycosidic bonds to prepare quercetin, process turmeric to extract and prepare diosgenin, and combine steam explosion and solid-state fermentation to convert Polygonum cuspidatum resveratrol glycosides to prepare resveratrol. In recent years, the technology of steam explosion pretreatment has been investigated for DF modification from a wide range of feedstocks, including wheat bran, grapefruit peel, okara, sugarcane bagasse, pineapple peel, citrus pomace, and vegetable waste [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Steam Explosion Technology Process and Principlementioning
confidence: 99%
See 1 more Smart Citation
“…There have been studies using steam explosion to hydrolyze rutin glycosidic bonds to prepare quercetin, process turmeric to extract and prepare diosgenin, and combine steam explosion and solid-state fermentation to convert Polygonum cuspidatum resveratrol glycosides to prepare resveratrol. In recent years, the technology of steam explosion pretreatment has been investigated for DF modification from a wide range of feedstocks, including wheat bran, grapefruit peel, okara, sugarcane bagasse, pineapple peel, citrus pomace, and vegetable waste [ 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Steam Explosion Technology Process and Principlementioning
confidence: 99%
“…Liu et al [ 90 ] used SE pretreatment to process sweet potato vine with different moisture content, and found that the hemicelluloses shoulder of manually dried feedstock samples’ derivative thermal gravimetric (DTG) curve almost disappeared after SE pretreatment, and the height of the maximum peak increased 12.5% and moved to a higher temperature due to the degradation of hemicelluloses and the related lifting of cellulose. In the study of Sui et al [ 66 ], the authors investigated SE processing on the deconstruction of wasted broccoli stems. The results showed that the SE process led to the removal of hemicelluloses, re-condensation of lignin, degradation of the cellulosic amorphous region, and enhancement of the thermal stability of broccoli wastes.…”
Section: Effect Of the Se On The Structure Of Dfmentioning
confidence: 99%
“…HA is a typical kind of HS that can be easily prepared from various biomass wastes via hydrothermal technology ( Shu et al, 2016 ; Wang J. et al, 2017 ; Chang & Huang, 2018 ; Yang et al, 2019 ; Malhotra & Garg, 2020 ; Sriramoju et al, 2020 ; Sui et al, 2021 ). Chang & Huang (2018 ) produced a value-added nutrient solution containing 17% of HA in HT by using sugarcane exocarp as the raw material.…”
Section: Biomass Waste Humification Processesmentioning
confidence: 99%
“…As for other types of biomass waste, similar phenomena can be observed. For instance, Sui et al (2021 ) used broccoli waste as the raw stock for hydrothermal humification to investigate the influence of the reaction temperature on the degree of humification. The humification rate calculated by the content of FA and HA increased from 0.16 to 0.25 as the reaction temperature increased from 184 to 220°C.…”
Section: Biomass Waste Humification Processesmentioning
confidence: 99%
See 1 more Smart Citation